As perspectivas educacionais como instrumento da proteção integral no combate a violência contra a criança e o adolescente - Costa, Nálbia Roberta Araújo da (2010)
This research has legal and sociological therefore proposes to investigate the effectiveness of the doctrine of full protection in combating violence against children and adolescents using the educational prospects as an instrument of defense. Considering the violence as a historical - social phenomenon, complex and multifactorial approaches to various forms of violence against children and adolescents, such as physical violence, psychological violence, neglect, sexual abuse and exploitation, and violence and environmental violence stemming from child labor. The objective is to include the new educational perspectives, found in the Brazilian legal system as an instrument of prevention and rehabilitation of children and adolescents. The justification of using the theme being addressed due to the interest of the researcher in seeking solutions to the rampant practice of juvenile violence that plagues so diurnally plague Brazilian society, and specifically the State of Paraíba. As a result it is clear that the international legal provisions and the Brazilian legal system, considering the 1988 Federal Constitution, the Statute of Children and Adolescents, 1990, the Law of Directives and Basis for National Education, Law on Environmental Education, both of 1996, among others, converge on the ideal of integral protection of children and adolescents, as well as the imminent necessity of its effectiveness, especially with regard to legal protection against violence. In this conception, are associated with the ideals of the right of children and adolescents, understanding of mutual social responsibility, with new perspectives found in educational and preventive measures to defend the interests of victimized children and adolescents.